(3fXe egedGJ GdHMhQs - (3GdSLGYj , CMeO Hf CMeO Hf eMeO GdSLGYj GdHOQGhj GdGRgQj, TgGH GdOjf,J (B1197 (3g` s
(3ChdgG (B:s
(3HOCJ HMeO Gddg oeUdjkG Ydi GdoeUWai NjQ GdHQGjG fHjfG hHYO aNP fXekG deG gh eged Ydi fSb ddNRQLj aCJbfG s
(3BNQgG (B:s
(3hUdi Ydi Wg hSde hBdg hCUMGHg Cgd GdecGQe hGdKfG JeJ HMeO Gddg Ydi jO fGXegG CMeO GdSLGYj GdTGaYj YaGGddg Yfg s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B93 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B154s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdYQhV hGdbhGais